MY SAY: Darwin's economic legacy - Abd Razak, Dzulkifli (2009)
Some 200 years ago, on Feb 12, Charles Robert Darwin was born in Shrewsbury, England. An eminent naturalist, he is noted for his idea on "natural selection", which later attempts to unify many theories in the life sciences. Talk about Darwin and the word "evolution" — the dominant theory that explains the origin of the diverse living species — jumps out almost spontaneously. So, too, the phrase "the survival of the fittest", though it was originally coined by English philosopher Herbert Spencer before him in 1851. This expression appeared only in Darwin's fifth edition of Origin of Species (1869).